CompTIA Security+ SY0-601 Exam Cram, 6th Edition - Barrett, Diane (Pearson IT Certification, 2020)
CompTIA® Security+ SY0-601 Exam Cram , is the perfect study guide to help you pass the newly updated version of the CompTIA Security+ exam. It provides coverage and practice questions for every exam topic. Extensive prep tools include quizzes, Exam Alerts, and our essential last-minute review Cram Sheet. The powerful Pearson Test Prep practice software provides real-time practice and feedback with two complete exams. Covers the critical information youll need to know to score higher on your Security+ SY0-601 exam! Assess the different types of attacks, threats, and vulnerabilities organizations face Understand security concepts across traditional, cloud, mobile, and IoT environments Explain and implement security controls across multiple environments Identify, analyze, and respond to operational needs and security incidents Understand and explain the relevance of concepts related to governance, risk, and compliance Exclusive State-of-the-Art Web-based Test Engine with Practice Questions Make sure youre 100% ready for the real exam! Detailed explanations of correct and incorrect answers Multiple test modes Random questions and order of answers Coverage of each current Security+ exam objective.
Title from content provider
Keywords: Computing Technology Industry Association; Computer networks -- Study guides -- Security measures -- Examinations; Computer security -- Study guides -- Examinations; Electronic data processing personnel -- Certification; Réseaux d'ordinateurs; Sécurité; Mesures; Examens; Guides de l'étudiant; Sécurité informatique; Examens; Guides de l'étudiant; Computer networks; Security measures; Examinations; Computer security; Examinations; Electronic data processing personnel; Certification; Study guides